SYNERGY OF GREEN WORK ENVIRONMENT AND SELF-EFFICACY IN ANSWERING THE BUSINESS TRANSFORMATION OF THE MEDICAL DEVICE INDUSTRY - Maulana, Alif; Firdaus, Vera; Puspita, Nindia Wahyu; Aprilia, Rizka Wahyu (PT. Antis International Publisher, 2025)
Objective: This study aims to find out whether the synergy of green work environment and self-efficacy can answer the business transformation in the medical device industry at PT. Sinaraya Nugraha Ahmadaris Medika. Method: The design of this study is quantitative with a descriptive approach. This study has a population of 166 employees and the sampling technique used is proportional random sampling so that 117 respondents who are employees of PT. Sinaraya Nugraha Ahmadaris Medika. The analysis technique used in this study is multiple linear regression analysis using SPSS version 22 for Windows. Results: The results of this study show that the variables of self-efficacy, green work environment, and work discipline have a positive effect on job satisfaction at PT. Sinaraya Nugraha Ahmadaris Medika. Novelty: This study uniquely integrates the Green Work Environment and Self-Efficacy as key factors influencing Job Satisfaction in the medical device industry. Unlike previous studies, this research utilizes observation, interviews, and questionnaires to provide a comprehensive analysis. Additionally, it highlights the role of work discipline as a moderating factor, offering a new perspective on how environmental sustainability and employee confidence drive business transformation and innovation.